Zeolite based foamed geopolymer concrete reinforced with Cellulose Nanofibril prepared in low concentration alkaline solution: Porosity, compressive strength, and water permeability - Tay, Chai Hua; Mazlan, Norkhairunnisa; Wayayok, Aimrun; Basri, Mohd Salahuddin; Albakri Abdullah, Mohd Mustafa (Elsevier, 2025)
Foamed geopolymer concrete is known for its sustainability and environmentally friendly attributes. However, it typically employs high concentrations of alkaline solution, ranging between 8M and 16M, thereby raising concerns about its high cost and negative impacts on humans and the environment. This study validates the geopolymerisation process of zeolite based foamed geopolymer concrete reinforced with Cellulose Nanofibril, prepared in low concentration of Potassium Hydroxide solution below 2M. This study also evaluates the geopolymer's properties in porosity, compressive strength, and water permeability. The alkaline solution used consists of seawater, Potassium Silicate, Potassium Hydroxide, and Potassium Chloride. Hydrogen Peroxide is used as foaming agents while Sodium Lauryl Ether Sulfate and Benzalkonium Chloride served as surfactants, with Cellulose Nanofibril as reinforcement for the foamed geopolymer concrete. Following mixing using a high shear stirrer and curing in an ambient temperature of 30 °C for a day, geopolymerization of samples was confirmed through immersion in boiling water, X-ray Diffraction analysis, and Fourier Transform Infrared Spectroscopy analysis. Response Surface Methodology on porosity revealed that the terms Sodium Lauryl Ether Sulfate/Benzalkonium Chloride and Hydrogen Peroxide/Cellulose Nanofibril had p-values of 0.000, while terms Seawater/Potassium Silicate and Potassium Hydroxide/Potassium Chloride had p-values of 0.360 and 0.279, respectively. A combination of high Sodium Lauryl Ether Sulfate and Hydrogen Peroxide yielded samples with porosity >45%. At maximized Hydrogen Peroxide, increasing concentration of Potassium Hydroxide solution increases the porosity up to 35%–40%. Additionally, the presence of Potassium Chloride in geopolymer slurry stabilized by surfactant Sodium Lauryl Ether Sulfate resulted in higher porosity. Optimization analysis predicted a porosity of 61.460% which was validated experimentally with an acceptable margin of error. Increasing the concentration of Potassium Hydroxide solution was found to result in higher porosity, higher compressive strength, and higher water permeability. Increasing the Cellulose Nanofibril content leads to a decrease in porosity and water permeability but an increase in compressive strength. As a result, this study revealed that optimizing the composition of geopolymer prepared in low concentration alkaline solution is critical for balancing the porosity, compressive strength, and water permeability, offering insights for cleaner production practice for construction materials.